Bioequivalence Analysis of Clindamycin Hydrochloride Capsules in Healthy Chinese Subjects Under Fasted and Fed Conditions - Wang, Zhi; Wen, Haitang; Qian, Xuebing; Huang, Min; Cheng, Guohua; Zhong, Guoping (Clinical pharmacology in drug development, 2025)
Clindamycin is a lincosamide antibiotic for the treatment of staphylococcal, streptococcal, and anaerobic bacterial infections. We conducted a single-center, single-dose, 2-preparation, 2-period, 2-sequence, randomized, open-label, 2 × 2 crossover study to evaluate the pharmacokinetics (PKs) and safety of the test and reference clindamycin hydrochloride capsules in healthy Chinese subjects under both fasted and fed conditions. Forty-eight subjects were enrolled in the study totally, with 24 subjects in each group. All subjects were asked to take a test or reference preparation, under either fasted or fed condition, and their blood samples were collected and assayed by a validated high-performance liquid chromatography-tandem mass spectrometry method. PK parameters including maximum plasma concentration, area under the plasma concentration-time curve from time 0 to the last concentration, and area under the plasma concentration-time curve from time 0 to infinity were estimated with noncompartmental model and analyzed. Results showed that the PK profiles of the 2 preparations were consistent and met the bioequivalence criteria. Food was identified as a factor that had an impact on clindamycin absorption. The safety of clindamycin hydrochloride capsules was satisfactory. This study proved that the 2 clindamycin hydrochloride capsules were bioequivalent in healthy Chinese subjects under both fasted and fed conditions.